Preparation of Knockout Extract by Immunoaffinity Column and Its Application - Osamu Morinaga; Nguyen Huu Tung; Takuhiro Uto; Yukihiro Shoyama (Antibodies, 2012)
Importance of herbal medicines have recently increased owing to rising interest in their health benefits. However, medicinal plant extracts are complex mixtures of phytochemicals that act synergistically or additively on specific and/or multiple molecular and cellular targets. Thus, it is difficult to examine the actual pharmacological roles of active compounds in plant extracts. This review describes a new strategy for isolating target compounds from plant extracts using immunoaffinity columns coupled with monoclonal antibodies (mAbs) against natural compounds. Through one-step purification using mAb-coupled immunoaffinity columns, we succeeded in preparing a knockout (KO) extract, which contains all components except the target compound. Furthermore, we investigated the pharmacological effects of the KO extract to reveal the actual effects of a bioactive compound in the crude extract. This approach may help determine the potential function of target compounds in herbal medicines.